Penerapan Teknik Relaksasi Nafas Dalam Kombinasi Terapi Dzikir Terhadap Kecemasan Pasien Pre Operasi - Ricky Zainuddin; Hayatul Fitri; Andi Arniyanti; Yantimala Mahmud; Nurbaiti Nurbaiti (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: PreOperative is a stage that begins when there is a decision to perform the surgical intervention and ends when the patient is sent to the operating table. Objective: Know the level of anxiety in preoperative patients. Method: This study uses a descriptive analysis design with a case study approach. Researchers made observations on two study subjects, and the study will be measured using the Hamilton Rating Scale for Anxiety (HARS) questionnaire. Result; Based on the results of measuring the level of anxiety in two samples during the visit, it showed a very significant decrease in the stress level. This is because both clients have been given therapy breath relaxation techniques in combination with dhikr therapy, which can improve alveoli ventilation, maintain gas exchange, prevent pulmonary atelectasis, and reduce physical and emotional stress. Conclusion; The application of breath relaxation techniques in combination with dhikr therapy can lower the level of anxiety in preoperative patients. It is therefore advisable for subsequent studies with more samples and a long time of therapy administration regarding applying breath relaxation techniques in combination with dhikr therapy to the anxiety of preoperative patients.